Regenerative potential of nanoenabled collagen-polylactide scaffolds for osteochondral defect repair in rabbits - Schröter, Lena; Teixeira, Graciosa Quelhas; de Roy, Luisa; Krüger, Benjamin Thilo; Küppers, Oliver; Leite Pereira, Catarina; Pereira Vasconcelos, Daniela; Lamghari, Meriem; Sarmento, Bruno; Klinkenberg, Geir; Schmid, Ruth; Gracia, Raquel; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
Current tissue engineering strategies for treating traumatic or degenerative cartilage defects in osteoarthritis (OA) remain insufficient in promoting robust tissue regeneration while simultaneously addressing inflammation, matrix degradation, and post-surgical infections. In this study, we evaluated the in vivo biocompatibility and regenerative potential of a nanoenabled collagen-polylactide (Col-PLA) scaffold functionalized with tri-combinatorial nanoemulsions delivering ibuprofen (anti-inflammatory), batimastat (BB-94, anti-proteolytic), and mupirocin (anti-bacterial). Using a femoral osteochondral defect model in New Zealand White rabbits, regeneration was assessed at 4- and 12-week post-implantation by macroscopic scoring, biomechanical indentation mapping, and histological analysis. Synovial inflammation was further evaluated via histology, CD8 immunostaining, and quantification of key pro-inflammatory mediators including interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), prostaglandin E2 (PGE2), and matrix metalloproteinase-13 (MMP-13). Both functionalized and non-functionalized Col-PLA scaffolds supported significant host cell infiltration and tissue regeneration, outperforming untreated controls and demonstrating effective subchondral bone repair. A transient inflammatory response was observed in the nanoenabled group at 4 weeks, without elevation of synovial pro-inflammatory cytokines or compromised tissue regeneration. Although cartilage repair was comparable between scaffold groups, the nanoenabled Col-PLA scaffold might have a potential benefit in more complex or comorbid clinical scenarios due to its immunomodulatory, anti-proteolytic, and anti-microbial functionalization. The findings of this study support further investigations of these modular scaffolds in OA and infection-prone environments, using disease-relevant and long-term models, to fully establish its therapeutic applicability in regenerative medicine.